Modeling of laminated veneer lumber - A study of the material properties for thick structural elements - Ek, John; Norbäck, Viktor (My University, 2020)
This thesis studies the material properties of laminated veneer lumber (LVL). LVL is a timber product made of thin veneers of wood, glued together to form a laminate. The work has been carried out with the aim of providing a better understanding of LVL when designing large structures, in particular the thesis is related to the large scale application of wind turbine towers. The project consists of two major parts, initially a study of the possibility to use laminate theory for evaluation of LVL stiffness parameters. From this study it was found that the laminate theory used, in combination with the accessible material parameters provide an unfit description of the material. Consequently the second part of the project investigates the material behaviour using a more advanced three dimensional model, taking the effect of variability in veneer properties and the influence of knots, modeled as stiffness free voids, into account. The study reveal that increasing the number of veneers, increases the effect from the variability of veneers and reduces the influence of knots. Conclusions from the model suggests there are both beneficial and unfavourable effects when designing thick LVL structures. In order to account for these effects which currently is not practice, a more elaborate three dimensional model need to be studied, analyzing the material further.
Keywords: Laminated veneer lumber (LVL); Laminate theory; Finite elements